Hubungan antara Sympathetic Hyperarousal dan Stres Akademik pada Mahasiswa - Risdiansyah, Risdiansyah; Rusdi, Fadhillah Putri (MESINA (Medical Scientific Journal), 2025)
Sympathetic hyper-arousal is a condition of excessive activation of the sympathetic nervous system and the hypothalamus–pituitary–adrenal (HPA) axis caused by prolonged stress exposure. Academic stress among university students is a prominent form of psycho-social stress that can disrupt the autonomic nervous system balance and induce physiological and psychological dysfunctions. Heart Rate Variability (HRV) and cortisol levels are widely used objective biomarkers to assess neural and hormonal responses to stress. This study aimed to evaluate the relationship between academic stress and sympathetic hyper-arousal in university students through a systematic review and meta-analysis of HRV parameters and cortisol levels. Following PRISMA 2020 guidelines, literature searches were conducted in PubMed using relevant keywords. Studies meeting inclusion criteria were quantitatively analyzed using RevMan 5.4 under a random-effects model. Quality was assessed with the Newcastle–Ottawa Scale (NOS), and bias and sensitivity analyses were performed to ensure validity. Of 387 identified articles, four studies involving 520 students aged 18–25 years met inclusion criteria. Meta-analysis revealed a significant decrease in HRV during academic stress (Hedges’ g = –0.61; 95% CI –0.94 to –0.28; p < 0.01; I² = 42%) and a significant increase in cortisol levels (Hedges’ g = 0.47; 95% CI 0.19–0.75; p = 0.003; I² = 26%). All studies used the Perceived Stress Scale to assess subjective stress, and study quality was good (NOS 7–9). Academic stress correlates with increased sympathetic activity and decreased parasympathetic regulation, indicated by reduced HRV and elevated cortisol. These findings highlight sympathetic hyper-arousal under academic stress and support the use of physiological stress management approaches such as mindfulness and HRV biofeedback in higher education.